Biodiversity Study of Algal Communities from Effluents of Certain Factories of North Maharashtra - S.N.Nandan, P.B. Nerpagar* and (Current Botany, 2011)
There are numerous reports dealing with floristic and ecology of lentic and lotic algae but the algal flora of waste water systems have been little investigated. The present investigation comprises chemical and biological assessment of the effluents from five sites of North Maharashtra region viz. i) Maharashtra Oil factory, MIDC Dhule ii) Deesan Agro Product, MIDC, Dhule. iii) Shraddha Paper Mills, Warkhedi, Tal. Dist. Dhule, iv) Belganga Sahakari Sugar Factory, Ltd Bhoras Tal Chalisgaon, Dist. JalgaonÃ‚Â  v) Siddharth Carbo-Chem Product Ltd. E3, MIDC, Jalgaon. Biodiversity of four groups of algae was made for two years. In present paper, 36 algal taxa were reported belonging to four groups of algae viz. Cyanophyceae (9), Chlorophyceae (8), Bacillariophyceae (11), and Euglenophyceae (6) from five factories of study area. Among four groups of algae the class Bacillariophyceae is dominant as compared to other groups in the present study.